Konsep Perkembangan Manusia Dalam Pemikiran Abraham Maslow Dan Implikasinya Dalam Pendidikan Islam - Albany, Sulistiono Shalladdin (Universitas Wahid Hasyim Semarang, 2023)
Problems in education are related to problems of life and human life. The educational process exists and develops in tandem with the process of human life and development. This research aims to examine the concept of human development in Abraham Maslow's thinking and its implications for Islamic education. This research is library research (literature review) using a comparative and inductive approach, namely exploring theories about human development that exist in the minds of figures and then examining their implications in Islamic education. The results of this research state that human nature according to Abraham Maslow is termed basic needs and metamotivation. The concept of human development according to Abraham Maslow is divided into five phases of a hierarchy of basic human needs, namely physiological, safety, belonging and love, self-esteem, self-actualization. Analysis of the concept of human development according to Abraham Maslow reveals the goal of human development to achieve maximum self-potential. The implications in Islamic education are for students and educators so that both can understand human tendencies in development and then tie them together with material components that support integral human development so that the goals of Islamic education can be achieved effectively.Kata Kunci : Abraham Maslow, Perkembangan Manusia, Pendidikan Islam